Talent management - Ismail, Fadillah; Rashid, Umi Kartini; Ahmad, Zanariah; al Hosain, Adnan Ali Hassan; Mohd Rosli, Nur Amalina (Penerbit Uthm, 2019)
Talents infer individuals as people, and are today portrayed as fundamental for an organization's economical upper hand (Lewis & Heckman 2006; Collings & Mellahi, 2009; Hartmann, Feisel & Schober; Tarique & Schuler, 2010) and augmenting hierarchical execution (Nijs, Gallardo-Gallardo, Dries & Sels, 2014). A talent is normally said to be hard to duplicate, mirror and to substitute (Larsen, 2012). Notwithstanding, the writing underlines that a "working definition" of the term is missing, where in a hierarchical setting, the term is characterized variously (Lewis & Heckman 2006), and this has made it hard to pick the "right" definition (Tansley, 2011). So as to legitimately characterize ability in an authoritative setting, and as per the target of this examination, three definitions were perceived as fitting: